Social Equality in Education France and England 1789-1939 - Doyle, Ann Margaret (Springer International Publishing, 2018)
This book explores the development of education in France and England from the French Revolution to the outbreak of World War II. The author uses social equality as a framework to compare and contrast the educational systems of both countries and to emphasise the distinctive ideological legacies at the heart of both systems. The author analyses how the French Revolution prompted the emergence of an egalitarian ideology in education that in turn was crucial for propagating the values of equality, patriotism and unity. In tandem, the volume discusses the equally dramatic consequences of the Industrial Revolution for English society: while England led the world by 1800 in trade, commerce and industry, a strict form of liberalism and minimal state intervention impeded the reduction of educational inequality. This pioneering book will be of interest to students and scholars of educational equality as well as the history of education in France and England.